Sex reversal induced by 17β-estradiol may be achieved by regulating the neuroendocrine system of the Pacific white shrimp Penaeus vannamei - Tao Wang; Shihao Li; Yang Yu; Fuhua Li (BMC Genomics)
Abstract Background Due to sexual dimorphism in growth of penaeid shrimp, all-female cultivation is desirable for the aquaculture industry. 17β-estradiol (E2) has the potential to induce the male-to-female sex reversal of decapod species. However, the mechanisms behind it remain poorly understood. This study aimed to investigate the effects of E2 immersion on the neuroendocrine system (the eyestalk ganglia, brain, thoracic ganglia, and ventral nerve cord) of the Pacific white shrimp Penaeus vannamei through comparative transcriptomic analyses of the control males (CM), E2-treated males without sex reversal (EM), and neo-females (NF). Results Immersion in E2 at 2 mg/l from post-larvae (PL) 5 to 85 results in a skewed female-to-male ratio of 2.56: 1. The survival rate remains unaffected by E2 exposure, while a notable inhibition in growth is exclusively observed in the EM compared to the CM group. The transcriptome analysis result indicates that the observed retardation in growth of the EM may be attributed to the potential neuronal damage caused by the excessive neurotransmission, which in turn disrupts the PI3K-Akt signaling and cell cycle pathways. In contrast, the negatively regulated pathways of neuroactive ligand-receptor interaction and the dopaminergic synapse in the NF group suggest a potential impact of E2 on neuroplasticity through the modulation of neuroregulator binding and signaling, which affects the establishment of morphological differences and gender identity. Moreover, the activation of steroidogenesis and the inhibition of the insulin signaling may be associated with the success of E2-induced sex reversal. With these findings, a proposed mechanism of neuroendocrine system in decapods in response to E2 exposure is presented. Conclusions The present study represents a first step in understanding the effects of E2 on the neuroendocrine system at the molecular level. The observed retardation in growth in the EM group may be attributed to the potential for neuronal damage and disruptions in the cell cycle and PI3K-Akt signaling pathways. Furthermore, the success of E2-induced sex reversal may be associated with the downregulation of neuroactive ligand-receptor interaction, dopaminergic synapse, and insulin signaling pathways, as well as the activation of steroidogenesis. These findings provide new insights into the mode of action of E2, and underscore the potential for large-scale production of all-female stocks in P. vannamei.